If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 99x + 44x = 44 + 100x Combine like terms: 99x + 44x = 143x 143x = 44 + 100x Solving 143x = 44 + 100x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-100x' to each side of the equation. 143x + -100x = 44 + 100x + -100x Combine like terms: 143x + -100x = 43x 43x = 44 + 100x + -100x Combine like terms: 100x + -100x = 0 43x = 44 + 0 43x = 44 Divide each side by '43'. x = 1.023255814 Simplifying x = 1.023255814
| (3a^2+1)-(4+2a^2)=0 | | 5p-4=16 | | -3=n/7 | | 18+3-12/6= | | 3x+5=7x-6 | | 11+4*x/(-5)=2/3 | | 9c^2+16c-4=0 | | 64/(9*3-19)= | | 2x+48=-77+3x | | (4+2n^3)+(5n+2)=0 | | 3x^0=0 | | 2x+48=77-3x | | 2x+48=77+3x | | (3+n)6=36 | | 5b^2+7b+6=0 | | 5b^2+7b+6=o | | 3x+2+x+3=x+3 | | 2x+8+3X+14=7X-2 | | 6x=2x | | (8u^2)-47u-6=0 | | 25-(11*2)+6= | | 6x-8=62 | | 3x+2+2x+1=x+3 | | x+(-4+2x)=4 | | 2x+48=168 | | 2x+48=-7x+168 | | -4a+7=a | | -8=(1/9)*(-9)*t+27 | | 9(2x+3)=-36-27(x+2) | | -5/8+m=1/3 | | -4x-7y=20 | | 8/5=2m+3/8 |